Analisis Pengalaman Pengguna pada Aplikasi Perangkat Bergerak Qlue dengan Pemetaan User Journey - Prima Rizki Maulidina; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Qlue is a smart city application on mobile devices, owned by PT. Qlue Performa Indonesia, in collaboration with the city government to handle public complaints. The main purpose of Qlue is as a bridge between the citizens and the city government to deliver public complaints about the surrounding environment. Based on preliminary observations, there are several problems related to the interface of Qlue that may impact the user experience. If the application does not provide a good user experience, users may leave the application and not use it again. User experience analysis aims to produce recommendations for improvements that can improve user experience of Qlue. By mapping the user journey, the author will gain insights of things that are interesting on Qlue, things that cause the respondents to experience difficulties, along with recommendations submitted by the respondent. Data needed for user experience analysis was collected through observation and interviews with respondents. Based on the results of the analysis, the most problematic features on Qlue are public forum, find friends, Street View, and navigation to page of details of neighborhood. The difficulties experienced by respondents when they want to use these features are difficult to find the location of features. There are several other difficulties experienced by respondents caused by misuse of labels and icons, as well as a lack of guidance. Recommendations for improvements are made in the form of design illustrations on the page, navigation, and icons that have problems.